The Importance of Crisis Management in Improving The Quality of Health Services for Patients in Hospitals in The Gaza Strip - ferouana, hazem ahmed (Finance and Business Economies Review, 2019)
Place the abstract here (the summary refers to the goal of the research, and the results obtained in two paragraphs). The study aimed to identify the level of crisis management in the detection of the level of crisis management and improve the quality of health services in Dar es Salaam Hospital. The most important results are that all the different dimensions of the different dimensions were close in terms of relative weights, obtained a relative weight of 78.05% The statistical average of the role of the employees towards improving the quality of health services has reached a relative weight of (70.88%). The correlation between statistical management, early warning, preparedness, containment of damages, Restore activity, education) and improve the quality of health services in MS Healed House Alsalam.ccant the most important results need to work for the management of the hospital to take all necessary measures to mitigate the effects of the crisis and reduce the continuing occurrence. Work on hospital management to take advantage of crisis management techniques in other departments in the country or in other countries with similar experiences. The general appearance of management should be appropriate with the nature of the services provided to the auditors.